Kompleksitas Ruang Publik (Public Space): Agora, Yunani dan Forum, Romawi - Yosica Mariana (ComTech: Computer, Mathematics and Engineering Applications, 2011)
The city that grows unplanned usually arises because of the conurbations of a culture, such as Agora in Greek and Forum in Roman. The “unplanned” city grows in strategic places, such as around the harbor, business places, worship places, or other activity centers. The city growth due to cultural centers is usually characterized by the growth of services as the economic support of the city activities. The service center develops a community center in the form of public facilities, such as public spaces and public buildings. Western understanding about this kind of design is oriented to functional vision illustrated from several illustrations of history that developed in the world of architecture. Understanding of cosmology in typology and morphology that affect the built environment, especially the face of a city, can be described by reviewing some of the phenomena that have been developed in connection with cosmological concept that affects the embryo of market formation, ie public open spaces which became the center of city residents to the commercial, political, recreational activities, and others resulting from the interaction of community activities.